FINANCIAL DISTRESS AND SUSTAINABILITY REPORT: PERSPECTIVE FROM FOOD AND BEVERAGE INDUSTRY - Widjaja, Aurellia Aretha Agustine; Yanti, Yanti (Graduate Program of Universitas Tarumanagara, 2025)
Stock return serves as a key indicator for investors in assessing the profit potential on their investment. Various factors influence stock return fluctuations, such as financial distress and sustainability reports. This research aims to examine the importance of considering these factors in investment decision-making, with a specific focus on food and beverage companies listed on Indonesia Stock Exchange. Financial distress is measured using Altman Z-Score, while sustainability reports are assessed through Sustainability Reporting Disclosure Index (SRDI). Using a purposive sampling method, this research analyzed 115 data samples from 41 companies over the period of 2021-2023. The research relies on secondary data, including financial statements, sustainability reports, and historical data of stock prices and dividends from each company. Thereafter, the data is processed and evaluated using Microsoft Excel and EViews 12. The findings confirm that financial distress has no significant effect on stock returns, while sustainability reports exert a significant negative impact. These findings provide valuable insights for companies’ stakeholders, as well as academics, to increase their awareness in financial distress and sustainability reports on stock returns performance. This research also offers valuable implications, particularly in enhancing the understanding of how financial distress and sustainability reports affect stock performance in the food and beverage industry.